(untitled) (Eurasian Journal of Engineering and Technology, 2026)
This article analyzes the causes, effects, and countermeasures of arable land degradation, which is currently becoming a global environmental problem, the stages of developing projects for the organization of green spaces and land development projects, and several important factors in the use of land resources.